2018
DOI: 10.1002/hrm.21922
|View full text |Cite
|
Sign up to set email alerts
|

High‐commitment work systems and middle managers' innovative behavior in the Chinese context: The moderating role of work‐life conflicts and work climate

Abstract: This study advances research on high‐commitment work systems (HCWSs) and organizational innovation by examining how the configuration of middle managers' work–family issues (i.e., work–family conflict and work climate for sharing family concerns) shape the relationship between HCWSs and innovation performance. Using a matched sample of senior management team members, middle managers, and frontline employees from 113 Chinese manufacturing firms and two waves of survey, we found that HCWSs are associated with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 79 publications
(176 reference statements)
5
62
0
4
Order By: Relevance
“…Indeed, the findings of Andreeva, Vanhala, Sergeeva, Ritala, and Kianto (2017), Lopez-Cabrales et al (2009), andZatzick andIverson (2006) do not support the "best practice" assertion. In the current literature, the negative influences of HPWS are understudied, and it is unclear what constrains HPWS's effectiveness (Chen, Jiang, Tang, & Cooke, 2018). From the contingency perspective, our findings suggest a double-edged effect of HPWS on innovation that is dependent on organization-specific contingencies (i.e., employee participation practices and human capital).…”
Section: Theoretical Implicationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, the findings of Andreeva, Vanhala, Sergeeva, Ritala, and Kianto (2017), Lopez-Cabrales et al (2009), andZatzick andIverson (2006) do not support the "best practice" assertion. In the current literature, the negative influences of HPWS are understudied, and it is unclear what constrains HPWS's effectiveness (Chen, Jiang, Tang, & Cooke, 2018). From the contingency perspective, our findings suggest a double-edged effect of HPWS on innovation that is dependent on organization-specific contingencies (i.e., employee participation practices and human capital).…”
Section: Theoretical Implicationsmentioning
confidence: 70%
“…Wright and Boswell (, p. 269) note that “(We) often hear of organizations that attempted to copy an HR practice or set of practices from a successful organization, only to find that the copied practices did not result in the same beneficial outcomes.” Indeed, the findings of Andreeva, Vanhala, Sergeeva, Ritala, and Kianto (), Lopez‐Cabrales et al (), and Zatzick and Iverson () do not support the “best practice” assertion. In the current literature, the negative influences of HPWS are understudied, and it is unclear what constrains HPWS's effectiveness (Chen, Jiang, Tang, & Cooke, ). From the contingency perspective, our findings suggest a double‐edged effect of HPWS on innovation that is dependent on organization‐specific contingencies (i.e., employee participation practices and human capital).…”
Section: Discussionmentioning
confidence: 99%
“…If the lecturer loses space and time to think, they will be less innovative. Supporting this assumption, previous studies revealed that the role conflict is negatively related to employee innovative work behaviours [19][20][21]. Further, the increased workload will decrease the innovation potential of employees [22].…”
Section: Teacher-researcher Role Conflict As the Predictormentioning
confidence: 84%
“…This is in line with the findings of previous studies. Role conflict has a negative effect on employees' innovative behaviour [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Wei and Lau (2010) argue that although there are subtle differences, the basic theme underlying these labels is similar: employees are viewed as valuable assets that firms can use to achieve a competitive advantage, and many authors use these labels interchangeably (Chen et al. 2018). We use the term ‘high commitment work system’ (HCWS).…”
Section: Introductionmentioning
confidence: 99%